Effects of muscle composition and architecture on specific strength in obese older women. Issue 10 (10th September 2015) - Rastelli, F.; Capodaglio, P.; Orgiu, S.; Santovito, C.; Caramenti, M.; Cadioli, M.; Falini, A.; Rizzo, G.; Lafortuna, C. L.
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Do obesity‐specific factors affect skeletal muscle performance in older individuals? What is the main finding and its importance? Older obese women have a larger quadriceps femoris size but develop lower tension per unit of skeletal muscle than their normal‐weight counterparts. Muscle impairment and excess body mass are very common among older people. Given that the effect of obesity on strength production has scarcely been studied in older individuals, we analysed functional and structural characteristics of quadriceps femoris (QF) in obese (OB) and normal‐weight (NW) older women with comparable habitual physical activity. In five OB (body mass index 36.8 ± 1.9 kg m−2, age 72.4 ± 2.3 years) and six NW well‐functioning older women (body mass index 24.3 ± 1.8 kg m−2, age 72.7 ± 1.9 years), peak knee‐extension torque (KET) was measured in isometric (90 deg knee flexion) and isokinetic conditions (240, 180, 120 and 60 deg s−1). Mid‐thigh QF cross‐sectional area (CSA) and muscle tissue fat content (MF%) were determined with magnetic resonance imaging (Dixon sequence). Muscle fascicle length and pennation angle (PA) were assessed with ultrasonography for each muscle belly of the QF (vastus lateralis, vastus intermedius, rectus femoris and vastus intermedius). Despite similar values of KET, CSA was 17.0% larger in OB than in NW women (P < 0.05), so that KET/CSA was significantly lower (P < 0.05) in OB women. Compared with NW women, OB women had 28.7% higher MF% (P < 0.05) and 24.9% higher average PA (P < 0.05), while fascicle length was similar. Overall, isometric KET/CSA was negatively affected by both MF% (P < 0.05) and PA (P < 0.05), while isokinetic KET/CSA was negatively affected only by MF% (P < 0.01). Muscle composition and architecture seem to be important determinants of KET/CSA in elderly women. In fact, owing to the effect of obesity overload, OB women have a larger QF size than NW women, but unfavourable muscle composition and architecture. The higher MF% and steeper PA observed in OB women are associated with reduced levels of muscle specific strength.